A Graphene/Gelatin Composite Material for the Entrapment of Hemoglobin for Bioelectrochemical Sensing Applications. Issue 7 (1st January 2016) - Thirumalraj, Balamurugan; Palanisamy, Selvakumar; Chen, Shen-Ming; De Wael, Karolien
Abstract : In the present work, a novel graphene (GN) and gelatin (GTN) composite was prepared and used as an immobilization matrix for hemoglobin (Hb). Compared with Hb immobilized on a bare, GN or GTN modified glassy carbon electrode (GCE), a stable and pair of well-defined quasi redox couple was observed at an Hb modified GN/GTN composite GCE at a formal potential of −0.306 V versus Ag|AgCl. The direct electrochemical behavior of Hb was greatly enhanced by the presence of both GTN and GN. A heterogeneous electron transfer rate constant ( K s ) was calculated as 3.82 s −1 for Hb immobilized at GN/GTN modified GCE, which indicates the fast direct electron transfer of Hb toward the electrode surface. The biosensor shows a stable and wide linear response for H2 O2 in the linear response range from 0.1 μM to 786.6 μM with an analytical sensitivity and limit of detection of 0.48 μAμM −1 cm −2 and 0.04 μM, respectively. The fabricated biosensor holds its high selectivity in the presence of potentially active interfering species and metal ions. The biosensor shows its satisfactory practical ability in the commercial contact lens solution and human serum samples.